1995
DOI: 10.1254/jjp.69.273
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Novel Prolyl Endopeptidase Inhibitor, JTP-4819, on Thyrotropin-Releasing Hormone-Like Immunoreactivity in the Cerebral Cortex and Hippocampus of Aged Rats

Abstract: ABSTRACT-We investigated the effects of a novel prolyl endopeptidase inhibitor, JTP-4819on thyrotropinreleasing hormone (TRH)-like immunoreactivity (TRH-LI) in the cerebral cortex and hippocampus of aged rats. The TRH-LI content of both brain regions in aged rats was significantly lower than that in young rats. A single oral dose of JTP-4819 (3 mg/kg) restored the cortical TRH-LI content in aged rats, while doses of 0.3 -3 mg/kg restored it in the hippocampus. Repeated oral administration of JTP-4819 at a dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 13 publications
2
13
0
Order By: Relevance
“…The levels of certain proline-containing peptides, such as substance P and TRH, have been reported to be decreased in the brain cortex and hippocampus of aged rats [Shinoda et al, 1995;Toide et al, 1997a, b]. Our study revealed decreases in the levels of activity of soluble PEP in the CNS during senescence.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…The levels of certain proline-containing peptides, such as substance P and TRH, have been reported to be decreased in the brain cortex and hippocampus of aged rats [Shinoda et al, 1995;Toide et al, 1997a, b]. Our study revealed decreases in the levels of activity of soluble PEP in the CNS during senescence.…”
Section: Discussionsupporting
confidence: 51%
“…This increased particulate PEP activity could be involved in the decreased levels of certain peptides such as AVP, TRH and substance P in old animals. These peptides are involved in senescence and have been suggested to be trophic factors for lower motor neurons [Shinoda et al, 1995;Toide et al, 1995b;Van den Bergh et al, 1996].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous in vivo studies have shown that administration of selective PEP inhibitors provokes a significant increase in the cerebral concentration of SP (Toide et al, 1996;Bellemère et al, 2003), ␣-MSH (Bellemère et al, 2003), AVP (Miura et al, 1995;Toide et al, 1996), and TRH (Shinoda et al, 1995;Toide et al, 1996). To determine whether PEP may be actually involved in the metabolism of these neuropeptides, the localization of PEPexpressing cells has been compared with the distribution of the mRNAs encoding the SP receptors NK1 and NK3, the ␣-MSH receptors MC3 and MC4, the AVP receptors V1a and V1b, and the TRH receptors TRH-R1 and TRH-R2 (Table 1).…”
Section: Involvement Of Pep In Neuropeptide Catabolismmentioning
confidence: 96%
“…This feature has motivated several research groups to explore the physiological roles of human POP family members and the therapeutic potential of their inhibitors to treat neurological, hormonal and metabolic disorders such as Alzheimer's disease, depression, abnormal blood pressure and type II diabetes. Two DPPIV inhibitors, vildagliptin and sitagliptin, are already in clinical use [8][9][10][11][12]. Due to their ability to cleave peptide bonds on the carboxyl end of proline residues, POP has also been studied as a potential therapeutic component for the treatment of celiac disease, a chronic enteropathy induced by immunotoxic and proline-rich gluten peptides [13].…”
Section: S9 Serine Protease Familymentioning
confidence: 99%